Adenoviral vectored vaccination protects against Crimean-Congo Haemorrhagic Fever disease in a lethal challenge modelResearch in context - Jack E. Saunders; Ciaran Gilbride; Stuart Dowall; Susan Morris; Marta Ulaszewska; Alexandra J. Spencer; Emma Rayner; Victoria A. Graham; Emma Kennedy; Kelly Thomas; Roger Hewson; Sarah C. Gilbert; et al. (EBioMedicine, 2023)
Summary: Background: The tick-borne bunyavirus, Crimean-Congo Haemorrhagic Fever virus (CCHFV), can cause severe febrile illness in humans and has a wide geographic range that continues to expand due to tick migration. Currently, there are no licensed vaccines against CCHFV for widespread usage. Methods: In this study, we describe the preclinical assessment of a chimpanzee adenoviral vectored vaccine (ChAdOx2 CCHF) which encodes the glycoprotein precursor (GPC) from CCHFV. Findings: We demonstrate here that vaccination with ChAdOx2 CCHF induces both a humoral and cellular immune response in mice and 100% protection in a lethal CCHF challenge model. Delivery of the adenoviral vaccine in a heterologous vaccine regimen with a Modified Vaccinia Ankara vaccine (MVA CCHF) induces the highest levels of CCHFV-specific cell-mediated and antibody responses in mice. Histopathological examination and viral load analysis of the tissues of ChAdOx2 CCHF immunised mice reveals an absence of both microscopic changes and viral antigen associated with CCHF infection, further demonstrating protection against disease. Interpretation: There is the continued need for an effective vaccine against CCHFV to protect humans from lethal haemorrhagic disease. Our findings support further development of the ChAd platform expressing the CCHFV GPC to seek an effective vaccine against CCHFV. Funding: This research was supported by funding from the Biotechnology and Biological Sciences Research Council (UKRI-BBSRC) [BB/R019991/1 and BB/T008784/1].